Dualism of the Pastoral and Social Existence of the Catholic Church in the Perspective of State Administrative Law: A Study of PMA Number 13 of 2025 - Suhartoyo Suhartoyo (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This study examines the dualism of the pastoral and social existence of the Catholic Church from the perspective of state administrative law, focusing on the Regulation of the Minister of Religion (PMA) Number 13 of 2025. This PMA regulates the Catholic religious legal body, distinguishing between pastoral work of an internal-spiritual nature and social work of a public-administrative nature. Normative analysis was carried out to assess the consistency of PMA with higher laws and regulations, such as the 1945 Constitution and the Government Administration Law. The results of the study show that PMA 13/2025 gives discretionary authority to the Minister of Religion and the Director General of Catholic Guidance, but it needs to be balanced with legal principles such as legality, justice, accountability, and transparency to prevent abuse of authority. This study recommends the proper implementation of these legal principles to improve the quality of government and the welfare of the community.